MANUAL DE PROCEDIMIENTOS CONTABLES Y TRIBUTARIOS PARA LA COOPERATIVA DE PRODUCCION Y COMERCIALIZACION AGROPECUARIA BALSAS AGROBALSAS. - Cordova Medina, Alex Javier (2024)
The present Curriculum Integration Work titled "MANUAL OF ACCOUNTING AND TAX PROCEDURES IN THE AGRICULTURAL PRODUCTION AND MARKETING COOPERATIVE BALSAS 'AGROBALSAS'." was carried out with the aim of assisting the Cooperative with a guide that will be of great utility for the development of accounting and tax procedures. It will also help optimize administrative and financial practices, ensuring compliance with current regulations and improving the operational efficiency of the Cooperative. Through a series of detailed and structured steps, a practical tool for the proper management of accounting and tax obligations will be provided, ensuring transparency and the correct management of resources. Each section of the manual has been designed to offer a clear understanding and practical application of the procedures, thus facilitating its adoption by the Cooperative's staff. It was established according to the needs of the cooperative, for which an interview was conducted with its diagnosis, allowing for a clear definition of the necessary procedures and policies, standard entries, and the respective flowcharts, facilitating their understanding and execution in a sequential and orderly manner for accounting and tax processes. This Curriculum Integration Work not only provides a solid theoretical framework but also offers practical and specific tools to improve the accounting and tax management of the Cooperative "AGROBALSAS." By following the guidelines and procedures established in this manual, it is expected that the Cooperative can achieve greater operational efficiency, ensuring compliance with regulations and transparency in the management of its financial resources.